Teachers' Awareness and Implementation of Gender Sensitivity in the Using of EFL Textbooks - Alkhotiyah, Afifatul Amala; Abid, Nuskhan (ITScience (Information Technology and Science), 2026)
This study aims to explore teachers' awareness and implementation of gender-sensitive language practices in the use of English as a foreign language (EFL) textbooks in secondary schools in Indonesia. This study uses a qualitative method with a case study design. The research participants consisted of secondary school teachers who actively teach English using EFL textbooks as the main material for daily learning. Data were collected through semi-structured interviews with teachers who met the criteria and were willing to participate in this study without coercion. Data were analyzed using thematic analysis to identify the main patterns that emerged from the interview results. The results of the study show two main findings. First, teachers are aware of gender representation, imbalance, and stereotypes in textbooks, and realize that textbooks are not entirely neutral materials. Second, this awareness is manifested in teaching practices through material modification, the use of gender-neutral language, character role adjustments, and critical discussions with students. These findings indicate that teachers act as pedagogical agents who can transform teaching materials to be more inclusive. This study also emphasizes the importance of gender literacy and pedagogical reflection in language education.